Microstrip sierpinski carpet antenna using transmission line feeding - A. Rahim, Mohamad Kamal; Abd. Aziz, Mohamad Zoinol Abidin; Abdullah, Noorsaliza (2005)
Low cost of fabrication and low profile features of microstrip antennas, attract many researchers to investigate the performance of this antenna in various ways. Today, fractal antenna become popular among the researcher because they have a peculiar properties that make them suitable for multiband applications. Microstrip Sierpinski carpet antenna using transmission line feed is proposed for a multiband operation. Bandwidth up to 47% is being obtained at frequency 7.93 GHz. The cross polar isolation is between 10 to 15 dB.